Near infrared sensitized exciton upconversion luminescence from inorganic perovskite nanocrystals - Yiyan Zhang; Tianyu Zhao; Yuming Deng; Xinyue Liu; Xiaorong Zhang; Tong Zhu; Hans Ågren; Guanying Chen (Nature Communications)
Abstract Lead halide perovskites serve as an important class of photoelectrical materials in modern technological applications, such as light emitting diodes, photodetectors, and solar cells. However, the inability to respond to near infrared light poses a tight constraint on their performances. This study reports a class of broadband near infrared-responsive inorganic lead halide perovskite nanocrystals, which emit a palette of tunable upconversion luminescence via organic dye-lanthanide tandem sensitization. The coordination of dyes (IR783) to the surface of ytterbium-doped cesium lead halide nanocrystals entails an intense and broad spectral response range of near infrared light (600-860 nm). Sub-10 Wcm−2 light irradiance at 804 nm induced ultrabright exciton luminescence (tunable from 520 to 625 nm), about 27,500 folds brighter than the one without dye sensitization, with upconversion brightness reaching 3.22 M−1cm−1. Transient absorption spectra revealed an ultrafast triplet energy transfer process (9.28 × 108 s−1) from dyes to ytterbium dopants with near-unity efficiency (98.4%), followed by cooperative sensitization that excites delocalized excitons. These broadband near infrared-responsive inorganic perovskite nanocrystals have implications for applications ranging from solar cells to near infrared imaging and sensing.